Decoding Agul Ku Payung Butut: A linguistic-psychological inquiry through Adler’s Theory of Inferiority - Muhammad Daffa Syafiq Nashr ad-Diba'i (Priviet Social Sciences Journal, 2025)
This study examines the Sundanese proverb “Agul ku Payung Butut” from the perspective of Individual Psychology, as elaborated by Alfred Adler. The proverb judges’ people on their pride about meaningless things, implying intricate psychological processes that can be explained by Adler’s ideas on inferiority feelings, compensation, and social interest. Using qualitative content analysis, the study combines semantic-metaphoric linguistic analysis with Adlerian psychological ideas. The research was based on the text of proverbs, the novel Payung Butut by Akhmad Bakri, and interviews with experts on Sundanese culture. The results show that the proverb depicts sick pay of inferiority complex whereby payung butut (worn out umbrella) signifies inferiority and agul (arrogance) as efforts to create artificial superiority. The wisdom of traditional Sundanese people proves to agree with psychological principles by highlighting genuine contributions to society instead of empty showiness. This adds to the understanding of the overlap between cultural manifestations and psychological processes, which applies to cultural psychology and linguistic research. This indicates that Sundanese proverbs can be used as a medium of psychological wisdom, informing human behavioral patterns that cut across cultures yet remain at the local cultural level.